Getting the Message Out: Why Mail-Delivered GOTV Interventions Succeed or Fail. Issue 1 (11th January 2023) - Fortier-Chouinard, Alexandre; Bodet, Marc André; Gélineau, François; Savoie, Justin; Ouimet, Mathieu
ABSTRACT: Mail-delivered get-out-the-vote (GOTV) field experiments have been found to increase voter turnout in some but not all contexts. We hypothesize that mail-delivered GOTV interventions are more successful in low-salience elections and test this in a systematic way for the first time. Relying on a systematic literature review and a meta-regression framework, we find that primary elections have a strong and significant positive impact on the success of mail-delivered GOTV interventions, whereas other commonly used measures of election salience, such as voter turnout, margin of victory, and a dummy for local elections, do not. These results highlight the possibility of fostering voter turnout using GOTV mail messages, especially in primary elections.